Ligand-Based and Structure-Based Investigation for Alzheimer's Disease from Traditional Chinese Medicine. (8th May 2014) - Liao, Kai Hsin; Chen, Kuen-Bao; Lee, Wen-Yuan; Sun, Mao-Feng; Lee, Cheng-Chun; Chen, Calvin Yu-Chian
Abstract : Alzheimer's disease is a neurodegenerative disease that was conventionally thought to be related to the sedimentation of beta-amyloids, but drugs designed according to this hypothesis have generally failed. That FKBP52 can reduce the accumulation of tau proteins, and that Tacrolimus can reduce the pathological changes of tau proteins are new directions away from the long held amyloid-beta-centric concept. Therefore, the screening of traditional Chinese medicine compounds for those with higher affinity towards FKBP52 than Tacrolimus may be a new direction for treating Alzheimer's disease. This study utilizes ligand-based and structure-based methods as the foundation. By utilizing dock scores and the predicted pIC50 from SVM, MLR, and Bayesian Network, several TCM compounds were selected for further analysis of their protein-ligand interactions. Daphnetoxin has higher affinity and complex structure stability than Tacrolimus; Lythrancine II exhibits the most identical trends in FKBP52 interactions as Tacrolimus, and 20-O-(2′ E, 4′ E -decadienoyl)ingenol may be further modified at its hydrocarbon chain to promote interaction with FKBP52. In addition, we observed the residue Tyr113 of FKBP52 may play a key role in protein-ligand interaction. Our results indicate that Daphnetoxin, 20-O-(2′ E, 4′ E -decadienoyl)ingenol, and Lythrancine II may be starting points for further modification as a new type of non-amyloid-beta-centric drug for Alzheimer's disease.